2021
DOI: 10.1186/s12884-021-04113-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of pregnant women with COVID-19 in Japan: a nationwide questionnaire survey

Abstract: Background Few reports have presented an overall view of pregnant women with coronavirus disease 2019 (COVID-19) across an entire country and throughout the entire gestation period. Furthermore, no such reports are available for Japan. We examined the clinical characteristics and outcomes of pregnant women with COVID‑19 on a national scale in Japan. Methods A nationwide questionnaire-based survey for all 2,185 maternity services in Japan was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…Our study examined a larger number of cases by subdividing the severity of the disease and found that severe cases were associated with late pregnancy (ie, the second half of the second trimester and later). Other reports of more cases requiring hospitalisation or severe cases in late pregnancy may support our results 7 9 11. The higher risk of severe illness in late pregnancy is similar to that of other respiratory viral infections, such as influenza 12 13.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our study examined a larger number of cases by subdividing the severity of the disease and found that severe cases were associated with late pregnancy (ie, the second half of the second trimester and later). Other reports of more cases requiring hospitalisation or severe cases in late pregnancy may support our results 7 9 11. The higher risk of severe illness in late pregnancy is similar to that of other respiratory viral infections, such as influenza 12 13.…”
Section: Discussionsupporting
confidence: 84%
“…7 8 We have already reported the clinical characteristics of infected pregnant women from January 2020, when the first cases of COVID-19 were reported in Japan, to June 2020, when the first wave of infection ended, showing that late pregnancy may be a risk factor for exacerbation of symptoms, and familial transmission is the most common route of infection. 9 The number of cases, including severe cases, was small, and further accumulation of cases and examination of the impact of infection on perinatal outcomes was the next issue. We investigated the risk factors of severe COVID-19 in pregnant women and the effect of severe cases on preterm birth based on the results of a nationwide questionnaire survey in Japan.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…From January to June 2020, an estimated 0.03% of pregnant women were confirmed to have COVID‐19 in 1418 facilities across the country. 25 Furthermore, a study reported that the number of neonatal intensive care unit admissions, neonatal resuscitation, and preterm birth decreased during the COVID‐19 outbreak, based on the administrative data of 186 hospitals. 26 To further assess this evidence, we examined the incidence of threatened abortion, threatened premature labor, and preterm birth before, during, and after the first state of emergency for COVID‐19 in 2020 in Japan, based on maternal reports.…”
Section: Introductionmentioning
confidence: 99%
“…Of these patients, 3 had a gestational age of 30 weeks or more; 2 cases (including this one) resulted in delivery during the treatment period against COVID-19. We performed a literature review of perinatal cases of COVID-19 in Japan [ [11] , [12] , [13] ], along with the first report of a 37-week pregnant woman with COVID-19 pneumonia who delivered a male newborn through a cesarean section in 2020 [ 14 ] ( Table 1 ). We searched for related articles by entering keywords ‘‘casirivimab, imdevimab, pregnant’’ into the PubMed database ( https://pubmed.ncbi.nlm.nih.gov/ ), and only one report described 2 cases of childbirth after treatment with C&I from the US in December 2021 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%